IMPROVING STUDENTS’ SPEAKING ABILITY BY RETELLING STORY WITH FLASH ANIMATION - Sukmawati, Nadya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research is to improve speaking ability of 8F students of Immanuel Junior High School in retelling a story with flash animation. The method used in this research was a classroom action research. Retelling story technique was used in this research. The researcher gave the test twice in two cycles. In this research, observation checklist, field note and rubric for assessing speaking were used in collecting the data. The teacher collaborated with the researcher during the action, observation, and reflection. Based on the speaking rubric the data showed the students speaking ability improved especially fluency and accuracy. The result shows the significant progress happened in every cycle. The mean score of first cycle was 55.79 (Poor) and the second cycle was 79.86 (Good). In addition from the percentage of fluency from cycle one to cycle two is 52.31% and 76.85%. The percentage of accuracy from cycle one to cycle two is 59.26% and 82.87%. This research implied that retelling story technique was good in teaching speaking and supported by flash animation as the media. Key Words: Improving, Speaking, Ability, Flash Animation, Retelling Story. Â Â